Numerical Solutions for Time-Fractional Cancer Invasion System With Nonlocal Diffusion - Manimaran, J.; Shangerganesh, L.; Debbouche, Amar; Antonov, Valery (Frontiers in Physics, 2019)
This article studies the existence and uniqueness of a weak solution of the time-fractional cancer invasion system with nonlocal diffusion operator. Existence and uniqueness results are ensured by adapting the Faedo-Galerkin method and some a priori estimates. Further, finite element numerical scheme is implemented for the considered system. Finally, various numerical computations are performed along with the convergence analysis of the scheme.